Morphological Spectrum of Congenital Anomalies of Kidney and Urinary Tract in Children: A Singlecenter Prospective Observational Study: Morphological Spectrum of CAKUT - Bhat, Nucksheeba Aziz; Mohd Ashraf; khan, 3. Naseer Ul Hassan; Muzafar Jan; sheikh, Rayees Yousuf; Sheikh , Quyoom Hussain; Sheikh, Waseem Shafi (Journal of Pediatric Nephrology, 2025)
Background and Aim: The range of congenital anomalies affecting the kidneys and urinary tract (CAKUT) is wide, extending from asymptomatic ectopic kidneys to severe bilateral kidney agenesis. This study unveils the spectrum of morphological anomalies in the kidneys and urinary tract among pediatric patients. Methods: Over 2 years, 116 patients underwent comprehensive evaluation, including lab tests, imaging, and radionuclide scans. Results: Among the 650 patients, 116 cases were identified as CAKUT, yielding a prevalence rate of 17.8%. Among these, 67 of 116(57.7%) were male, with the majority (85%) aged 0 to 5 years. Abnormal ultrasonographic findings drove hospital visits in 46 of 116(39.7%) cases, followed by recurrent fevers (19.8%), and urinary dribbling (12%). Anemia and renal dysfunction were the main lab abnormalities in 90 of 116(77.5%) and 40 of 116(34.5%) subjects, respectively. Meanwhile, CAKUT cases were categorized as non-obstructive in 78 of 116(68.1%) and obstructive in 37 of 116(31.9%), Primary vesicoureteral reflux (VUR) in 25/116 (21.6%) and ureteropelvic junction obstruction (UPJO) in 18/116 (15.6%) were most common non-obstructive and obstructive anomalies respectively. Among VUR cases, grade II and grade III VUR accounted for 9 of 25(36%) and 7 of 25(28%) subjects, respectively; also, aspects associated with hypertension were in 18 of 25(72%) and renal scarring in 4 of 25 (16%). UPJO was present in 18 of 116(15.5%) and typically mild in 14 of 18(61%) on ultrasonography (USG). Posterior urethral valves (PUV) accounted for 16 in 116(13.7%) of cases, presenting with renal dysfunction in 13 of 16(81%) and hydronephrosis in 12 of 16 (75%). Conclusion: This study provides valuable insights into the prevalence, clinical patterns, and morphological diversity of CAKUT. These findings underscore the importance of early diagnosis and multidisciplinary management for optimizing outcomes.